Get your team to do what it says it's going to do : how to close the gap between knowing and doing - Gant Halvorson, Heidi (2014)
Points out that creating goals that teams and organisations will actually accomplish isn't just a matter of defining what needs doing, but that the specifics have to be spelt out. Adds that recent studies indicate that if-then planning improves team performance by sharpening group focus and prompting members to carry out key activities in a timely manner.